Pulmonary tuberculosis specificities in smokers - Rhanim Aziza; Hammi Sanae; Kouismi Hatim; Jamal Eddine Bourkadi (Egyptian Journal of Chest Disease and Tuberculosis, 2015)
Background: Smoking and tuberculosis are two major challenges in public health system. The aim of our study is to identify the impact of smoking on clinical, radiological manifestations and evolutive pulmonary tuberculosis. Methods: This retrospective case–control study examined the files of 104 patients. The patients monitored for pulmonary tuberculosis were divided into 2 groups. We studied the clinical and radiological profile, and evolution in both groups. Results: 104 patients were included, divided into two groups: Group I: 59 current smokers who have tuberculosis (TB) and Group II: 45 TB patients who have never smoked. The mean age is 38 years. All patients in Group I are male while there is no predominance of one sex over the other in group II. The time to diagnosis is delayed in patients who smoke. There is no significant difference in the clinical symptoms. Radiological lesions are diffuse among current smoker patients, as they are mostly unilateral in group II. The clinical outcome was good in 91.1% of TB non smoking patients with weight gain between 2 and 5 kg versus 35.3% in the group of smokers. Bacteriological conversion in the second month was reached in 95.6% of patients in group II, while there was a bacteriological negativity delay in group II patients. Three smoking patients died. Conclusion: Our study raised the harmful impact of smoking on the clinical and radiological presentation of tuberculosis, and late bacteriological negativity, therefore we need to integrate smoking control into the national TB control program.